2018
DOI: 10.1007/s40520-018-1077-8
|View full text |Cite
|
Sign up to set email alerts
|

A new decision tree for diagnosis of osteoarthritis in primary care: international consensus of experts

Abstract: Background and aims Although osteoarthritis (OA) is managed mainly in primary care, general practitioners (GPs) are not always trained in its diagnosis, which leads to diagnostic delays, unnecessary resource utilization, and suboptimal patient outcomes. Methods To address this situation, an International Rheumatologic Board (IRB) of 8 experts from 3 continents developed guidelines for the diagnosis of OA in primary care. The focus was three major topologies: hip, knee, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
0
39
0
7
Order By: Relevance
“…Our study therefore lends further credence to the argument that in the clinical setting where the focus of intervention is on the improvement of symptoms, the use of a clinical definition of knee OA, which includes pain, may be more useful than relying on a radiographic diagnosis alone to identify individuals at risk of functional impairment and target resources accordingly. Indeed, the International Rheumatologic Board (IRB) recently proposed guidelines for the diagnosis of OA in primary care which are based on the ACR criteria for clinical OA [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our study therefore lends further credence to the argument that in the clinical setting where the focus of intervention is on the improvement of symptoms, the use of a clinical definition of knee OA, which includes pain, may be more useful than relying on a radiographic diagnosis alone to identify individuals at risk of functional impairment and target resources accordingly. Indeed, the International Rheumatologic Board (IRB) recently proposed guidelines for the diagnosis of OA in primary care which are based on the ACR criteria for clinical OA [23].…”
Section: Discussionmentioning
confidence: 99%
“…In routine clinical practice in Spain, patients with moderate-to-severe OA chronic pain refractory to standard analgesic treatment with NSAIDs plus opioids reported modest reduction in pain, while presenting a considerable burden of comorbidities, cognitive impairment, and level of dependency in a relatively short period of treatment Consequently, healthcare costs per patient significantly increased for the NHS, particularly when considering treatments with strong opioids; €2472/year vs. €1380/ year with weak opioids INTRODUCTION Osteoarthritis (OA) is a degenerative joint pathology with prevalence varying depending on the affected joint and the criteria used to define the disease [1,2]. Between 6% and 24% of adults have OA with chronic pain of more than 3 months' duration, with incidence increasing with aging [3][4][5]. In Spain, the study on prevalence of rheumatic diseases (EPISER) showed a prevalence of OA in any joint of 29.4% in persons aged over 40 years [5].…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…The increasing prevalence of OA is likely due to increases in longevity and prevalence of obesity 2,3. Clinically, the diagnosis of OA is mainly based on symptoms and radiographic findings, although discordance between pain and severity of radiographic joint pathology has been reported 4,5. The major histopathological changes in OA joint are the cartilage destruction with hypertrophic differentiation of chondrocytes 6.…”
Section: Introductionmentioning
confidence: 99%